2015
DOI: 10.1103/physrevb.92.125122
|View full text |Cite
|
Sign up to set email alerts
|

Nature of chiral spin liquids on the kagome lattice

Abstract: We investigate the stability and the nature of the chiral spin liquids which were recently uncovered in extended Heisenberg models on the kagome lattice. Using a Gutzwiller projected wave function approach -i.e. a parton construction -we obtain large overlaps with ground states of these extended Heisenberg models. We further suggest that the appearance of the chiral spin liquid in the time-reversal invariant case is linked to a classical transition line between two magnetically ordered phases.Introduction -The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
100
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 65 publications
(83 reference statements)
9
100
0
Order By: Relevance
“…where J φ = cos φ ∝ h. As we previously mentioned, the scalar spin chirality breaks time-reversal (T ) symmetry macroscopically and can be spontaneously developed in CSL [1][2][3][4][5][6][7][8]. Its effects on the magnetic excitations should be the same in the ordered and disordered phases.…”
Section: Topological Magnetic Excitationsmentioning
confidence: 98%
See 2 more Smart Citations
“…where J φ = cos φ ∝ h. As we previously mentioned, the scalar spin chirality breaks time-reversal (T ) symmetry macroscopically and can be spontaneously developed in CSL [1][2][3][4][5][6][7][8]. Its effects on the magnetic excitations should be the same in the ordered and disordered phases.…”
Section: Topological Magnetic Excitationsmentioning
confidence: 98%
“…But herbertsmithite ZnCu 3 (OH) 6 Cl 2 has D ⊥ /J ∼ 0.08 [30], thus remain a QSL. An applied magnetic field (H ⊥ 2D plane) can induce noncoplanar spin textures with a nonzero scalar spin chirality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important one is the Kitaev model on the decorated honeycomb lattice [23], which can be solved exactly by a mapping to Majorana fermions. In addition, strong numerical evidence for a CSL regime has been found in models of broken [25,26] and conserved [27][28][29][30][31] SU (2) spin symmetry on the kagome lattice, where competing magnetic order is sufficiently frustrated. From the viewpoint of symmetry classification, SU(2) symmetry is not a characteristic feature of CSLs.…”
mentioning
confidence: 99%
“…Several recent investigations have been focused on s > 1/2 [10,[19][20][21][22][23][24][25], anisotropic models [16,[25][26][27][28][29][30][31][32][33][34] as well as KAFMs with further-neighbor couplings [31,[35][36][37][38][39][40][41][42][43][44][45][46][47][48]. It has been found that such modifications of the pure KAFM may play a crucial role either to modify the QSL state or even to establish GS magnetic LRO of √ 3 × √ 3 or of q = 0 symmetry.…”
mentioning
confidence: 99%